2010
DOI: 10.1186/1471-2180-10-101
|View full text |Cite
|
Sign up to set email alerts
|

The analysis of oral microbial communities of wild-type and toll-like receptor 2-deficient mice using a 454 GS FLX Titanium pyrosequencer

Abstract: BackgroundAlthough mice have long served as an animal model for periodontitis, information on the composition of their indigenous oral microbiota is limited. The aim of the current study was to characterize mouse oral bacterial flora by applying extensive parallel pyrosequencing using the latest model pyrosequencer, a Roche/454 Genome Sequencer FLX Titanium. In addition, the effect of Toll-like receptor (TLR) 2 deficiency on oral microbiota was evaluated.ResultsEight oral bacterial communities of wild-type (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
140
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(152 citation statements)
references
References 24 publications
9
140
0
3
Order By: Relevance
“…All three isolates or their close relatives have been identified in mice oral cavities from a separate study using 454-pyrosequecning analysis (Chun et al, 2010), however, their physiological or biological functions have not been investigated. Our synthetic community data demonstrated that the E. coli-induced colonization resistance required the participation of these three Microbial social structure involved in colonization resistance X He et al players, and missing any one of them resulted in a greatly reduced colonization resistance against the integration of E. coli.…”
Section: Discussionmentioning
confidence: 99%
“…All three isolates or their close relatives have been identified in mice oral cavities from a separate study using 454-pyrosequecning analysis (Chun et al, 2010), however, their physiological or biological functions have not been investigated. Our synthetic community data demonstrated that the E. coli-induced colonization resistance required the participation of these three Microbial social structure involved in colonization resistance X He et al players, and missing any one of them resulted in a greatly reduced colonization resistance against the integration of E. coli.…”
Section: Discussionmentioning
confidence: 99%
“…To ensure the relative symbiont purity in the nucleic acid extractions, we examined the microbial composition of the 16S ribosomal RNA gene (V1-V3 region) via pyrosequencing, according to Chun et al (2010) (see Supplementary Methods for more details). Subsequent genomic analysis was performed on two samples that were determined to be relatively pure, one from each symbiont type, based on dominance of the target Oceanospirillales symbiont, which comprised 84% and 56% of the recovered 16S rRNA barcodes for symbionts Rs1 and Rs2, respectively (Supplementary Figure S1).…”
Section: Sample Collectionmentioning
confidence: 99%
“…At present, the 454 pyrosequencing technology has been widely used to reveal microbial diversity and ecology in different natural environments, such as the deep sea (Sogin et al, 2006;Huber et al, 2007), extreme hydrogeological conditions (Edwards et al, 2006) and soil (Leininger et al, 2006;Roesch et al, 2007). In addition, multiplexed high-throughput pyrosequencing of individual genes (for example, 16S rRNA) by tagging or bar coding with short nucleotides (also called pyrotag sequencing ) Parameswaran et al, 2007;Roesch et al, 2007;Hamady et al, 2008) has been developed to process many samples simultaneously and has been widely used in microbial community studies (Youssef et al, 2009;Cheung et al, 2010;Chun et al, 2010;He et al, 2010a, b;Koopman et al, 2010;Schutte et al, 2010;Teixeira et al, 2010;Uroz et al, 2010). A similar strategy has also been used for sequencing functional genes (Iwai et al, 2010).…”
Section: Introductionmentioning
confidence: 99%